Deep grace in deep space? How to become an astrotheologian. Issue 2 (2nd June 2022) - Peters, Ted
Abstract: If God's grace is already present to outer space, then Christian doctrines such as creation and redemption become as public as outer space is public. The public Christian theologian should engage in astrotheology as well as astroethics. This article tenders seven steps toward becoming an astrotheologian and astroethicist. (1) Become sensitive to the Beyond and the Intimate when talking about the true God. (2) Think cosmically. (3) Do not be bullied by the Cosmological Principle or the Copernican Principle. (4) Explore deep incarnation in deep space. (5) Add eschatology to deep incarnation. (6) By using a Theology of Culture, demarcate science, scientism, and pseudoscience. (7) Celebrate the 60th Anniversary of Astroethics. These steps presuppose a comprehensive hypothesis: the historical incarnation of the divine Logos in Jesus of Nazareth on Earth is constituted by the exchange of divine and creaturely attributes, the communicatio idiomatum ; and, when communicatio idiomatum is combined with an eschatological vision of God's promised new creation, we can accompany the entire material history of all galaxies and all extraterrestrial creatures into the eternal perichoresis of God as Trinity.